Analisis Pengaruh Taksasi Penjualan Bibit Kelapa Sawit pada Daerah di Kebun Lingkup Unit Marihat Tahun 2021-2023 - Arifah Nasution; Sri Sudiarti (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This research aims to determine the influence and analysis of sales of palm oil seeds in the area around the Marihat unit from the largest percentage of sales of seeds in the current year. This research was carried out at an oil palm plantation in the Marihat unit plantation in January 2023. This research used a quantitative descriptive method, namely by collecting secondary data obtained from the company. The research data were analyzed using the t test at a real level of 5%. The results of the research show that the accuracy of e-census in taxation is that there is a significant difference between the e-census fresh fruit bunch yields and the actual production fresh fruit bunch yields expressed in the difference between fresh fruit bunches and the percentage error. The results of this research show that the use of e-census in assessing palm oil production provides inaccurate results in terms of production realization by reviewing the factors that cause production targets to decrease.